2015
DOI: 10.1097/acm.0000000000000897
|View full text |Cite
|
Sign up to set email alerts
|

Four-Year Educational and Patient Care Outcomes of a Team-Based Primary Care Longitudinal Clerkship

Abstract: Incorporating students longitudinally into primary care clinics is highly rated by students. The ECMH model led to improved continuity, improved perceptions of the learning climate, and higher patient centeredness. Preliminary data suggest that students add value and improve patient outcomes during longitudinal clinical experiences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 32 publications
2
30
0
Order By: Relevance
“…These findings corroborate and extend upon a previous study [3] that showed that an ECMH-modeled longitudinal clerkship is associated with quantitative benefits to patient care. Our study further advances that work by demonstrating significantly increased screening rates for several measures in the ECMH model compared with standard clinical SVFCs, including those that were not specifically targeted for intervention.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…These findings corroborate and extend upon a previous study [3] that showed that an ECMH-modeled longitudinal clerkship is associated with quantitative benefits to patient care. Our study further advances that work by demonstrating significantly increased screening rates for several measures in the ECMH model compared with standard clinical SVFCs, including those that were not specifically targeted for intervention.…”
Section: Resultssupporting
confidence: 91%
“…In 2015, Henschen et al demonstrated improvements in cancer screening rates after implementation of a longitudinal clerkship called the education-centered medical home (ECMH) [3]. An ECMH is based on principles of the patient-centered medical home, including ‘continuity with a personal physician; team-based care; care coordination and integration; quality and safety; and enhanced access to care’ [11].…”
Section: Introductionmentioning
confidence: 99%
“…LICs and primary care are a natural fit, both emphasizing patient-centered care and continuity relationships among students, faculty, and patients, which can also have positive effects on students' primary care career selection. [12][13][14] Students in LICs experience continuity across multiple dimensions-Bcontinuity of patient contact and care, continuity of assessment and supervision, and continuity of clinical and cultural learning through patients, peers, health providers, and community health and social resources^. 15 Continuity with preceptors is especially important as they play a key role in shaping students' perceptions of primary care careers.…”
Section: Introductionmentioning
confidence: 99%
“…8 The reviews by Thistlethwaite and by Walters, and a later article by Henschen, showed that both longitudinal attachments in the community and LICs have a positive, though modest, effect on students' patient-centeredness. 6,9,10 As the decline in patient-centeredness takes place during the clinical years, it seems preferable to implement longitudinal student-patient relationships in this period. Up to now, LICs typically have been implemented in small cohorts of, on average, 20 students (range ¼2-85).…”
Section: Introductionmentioning
confidence: 99%